The Inflammasomes: Revamping Periodontal Pathogenesis - Nazreen Ansari; Jose Paul; Johnson Prakash D’Lima; Senny Thomas Parackal (New Frontiers in Medicine and Medical Research Vol. 7, 2021)
The world of medicine has recently been flummoxed by the discovery of inflammasomes which are assumed to regulate the host immuno-inflammatory responses. They are believed to have a multitude of purposes in the process, many of which, still remain to be elucidated. It has been observed that certain sensor proteins are required to assemble these inflammasomes in response to microbial components called PAMPs (pathogen associated molecular patterns) or endogenous molecules called DAMPs (damage associated molecular patterns). In most cases, inflammasomes have been demonstrated to undergo a process consisting of two steps to get activated. Furthermore, according to research, this involves various families of sensor proteins which play a part in the pathogenesis of many diseases, including periodontal disease through a number of corresponding pathways. This piece of information, thereby, affords us the opportunity to explore further and search for new targets to modulate host responses to microbial challenges.